A RARE CASE OF CHONDROMA OF CARTILAGINOUS NASAL SEPTUM - P., Shrinath D. Kamath; Shetty, Kishore; Shetty, Anusha; Mathias, Michelle; Rent, Natashya (Journal of Health and Allied Sciences NU, 2014)
Chondroma is a benign tumor of cartilaginous origin. Nasal septal chondromas are rare and almost always arise from the bony septum. Considering the very rare occurrence of chondroma from anterior part of the septum, we report a case of Chondroma of the nasal septal cartilage in an adult female, who presented with progressive unilateral nasal obstruction. CT scan showed the minimally enhancing lesion from the anterior septum confined to the left nasal cavity. Excision of the mass was done endoscopically. Histopathological examination of the specimen was suggestive of chondroma.
Keywords: Chondroma; Nasal septum; Endoscopic excision